2017
DOI: 10.1007/s00216-017-0471-y
|View full text |Cite
|
Sign up to set email alerts
|

A label-free electrochemical biosensor based on tubulin immobilized on gold nanoparticle/glassy carbon electrode for the determination of vinblastine

Abstract: Vinblastine (VLB) is prescribed for a wide variety of cancers. Therefore, development of sensitive methods for early diagnosis is urgently required. In this work, a highly sensitive and label-free impedimetric biosensor was fabricated for the electrochemical detection of VLB. First, the gold nanoparticles (AuNPs) were electrodeposited on the surface of a glassy carbon electrode (GCE). 3-Mercaptopropionic acid (MPA) was self-assembled over the AuNPs. Then, tubulin (TUB), as a receptor, was covalently immobilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Indirect determination of vincristine [208] and vinblastine [209] (both vinca alkaloids and analogs) was realized [199] with permission from Elsevier; (B) GCE surface sequential modification with AuNPs, MPA layer further used as the TUB anchor. The presented architecture was employed as the impedimetric vinblastine sensor.…”
Section: Plant Alkaloids and Other Natural Productsmentioning
confidence: 99%
“…Indirect determination of vincristine [208] and vinblastine [209] (both vinca alkaloids and analogs) was realized [199] with permission from Elsevier; (B) GCE surface sequential modification with AuNPs, MPA layer further used as the TUB anchor. The presented architecture was employed as the impedimetric vinblastine sensor.…”
Section: Plant Alkaloids and Other Natural Productsmentioning
confidence: 99%
“…Glassy carbon, which has the advantage of a wide potential window [12], is a popular choice for the supporting electrode. For example, a biosensor for the anti-cancer agent vinblastine was constructed by first electrodepositing gold nanoparticles onto a glassy carbon electrode (GCE) [13]. Electrodeposition was carried out in 3 mM of HAuCl 4 and 0.5 M of H 2 SO 4 at −0.20 V (versus Ag/AgCl) for 220 s. Scanning electron microscopy (SEM, MIRA3, TESCAN, Brno-Kohoutovice, Czech Republic) revealed a layer of gold nanoparticles of fairly uniform coverage; some of the nanoparticles were irregular in shape or in contact with their neighbors, and each of them was about 20 nm in size, as shown in Figure 1.…”
Section: Deposition At a Constant Potential For A Fixed Time Periodmentioning
confidence: 99%
“…The result of a limit of detection of 0.21 µM and two linear ranges extending up to 16.8 mM [105] is also noteworthy, although it is not clear why two distinct linear ranges occur. Some studies have reported the detection of H 2 O 2 by direct electron transfer between immobilized HRP and the electrode surface [13,21,25], and the results for HRP physisorbed on gold nanoparticles on ITO glass seem most attractive, offering both a low limit of detection of two µM and an extended linear range of up to 30 mM. As has been proposed [1], sensors working on direct electron transfer require minimizing the distance between enzyme active sites and the gold nanoparticle or nanostructure surface.…”
Section: Comparison Of the Advantages And Performance Of Different Nanostructuresmentioning
confidence: 99%
“…13,14 Different methods have been reported in the literature for the determination of vinblastine including spectrophotometry, 15,16 thin layer chromatography, 17 high-performance liquid chromatography, [18][19][20][21][22][23][24][25][26] capillary electrophoresis, [27][28][29][30][31] and voltammetric methods. [32][33][34][35][36][37] As far as the authors' knowledge, no potentiometric sensor is reported in the literature for the determination of vinblastine. Therefore, it was our concern to develop a simple, sensitive, and selective method for the quantitative analysis of such a life-saving drug, taking advantage of the superior inherent benets of ion-selective electrode-potentiometry such as simplicity, portability, rapidity, and lower energy consumption.…”
Section: Introductionmentioning
confidence: 99%